2013
DOI: 10.1016/j.ajpath.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Brucella abortus Induces Collagen Deposition and MMP-9 Down-Modulation in Hepatic Stellate Cells via TGF-β1 Production

Abstract: In patients with active brucellosis, the liver is frequently affected by histopathologic lesions, such as granulomas, inflammatory infiltrations, and parenchymal necrosis. Herein, we examine some potential mechanisms of liver damage in brucellosis. We demonstrate that Brucella abortus infection inhibits matrix metalloproteinase-9 (MMP-9) secretion and induces collagen deposition and tissue inhibitor of matrix metalloproteinase-1 secretion induced by hepatic stellate cells (LX-2). These phenomena depend on tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…B. abortus infection inhibits basal levels of MMP-9 secretions and induces collagen deposition and TIMP-1 secretion by hepatic stellate cells. These phenomena were dependent on TGF-␤1 induction (16). As occurs in other bacterial infections (41,42), a fibrotic phenotype may contribute to the persistence of infection, leading to poor penetration of antibiotics and immune mediators into the lesion.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…B. abortus infection inhibits basal levels of MMP-9 secretions and induces collagen deposition and TIMP-1 secretion by hepatic stellate cells. These phenomena were dependent on TGF-␤1 induction (16). As occurs in other bacterial infections (41,42), a fibrotic phenotype may contribute to the persistence of infection, leading to poor penetration of antibiotics and immune mediators into the lesion.…”
Section: Discussionmentioning
confidence: 94%
“…In this context, hepatic stellate cells have a fundamental role in tissue homeostasis and injury repair through the production of extracellular matrix proteins (33). We have demonstrated that infection of LX-2 cells with Brucella inhibits the spontaneous secretion of MMP-9 (as determined by ELISA and by measurement of its activity by zymography) and induces collagen deposition (16). To determine whether intracellular replication is critical for inhibition of MMP-9 secretion and for induction of collagen deposition, experiments were performed using the B. abortus virB10 mutant and the RB51 rough mutant.…”
Section: B Abortus Induces a Profibrogenic Phenotype In Lx-2 Cells In Amentioning
confidence: 91%
See 2 more Smart Citations
“…60 Briefly, 50  μ l of neutrophil supernatants (1 × 10 6 cells/ml) were mixed with 10  μ l of 5 × loading buffer (0.25 M Tris pH 6.8, 50% glycerol, 5% SDS, and bromophenol blue crystals) and loaded onto 10% SDS-PAGE gels containing 1 mg/ml gelatin (Sigma-Aldrich). Following electrophoresis, gels were washed using a solution with 50 mM Tris-HCl, pH 7.5, and 2.5% Triton X-100 (buffer A) for 30 min.…”
Section: Methodsmentioning
confidence: 99%